OPTIMALISASI STRATEGI KOMUNIKASI DALAM PROMOSI EDUKASI HIDROPONIK DI XFARM HOUSE PAMULANG TANGERANG SELATAN - Annisa Eka Mardiyah; Fatimatuzahrotul AINI (LPPM STAI Muhammadiyah Probolinggo, 2026)
This Community Service activity focuses on optimizing communication strategies in promoting hydroponic education at XFarm House, South Tangerang. The background of this activity stems from the limited effectiveness of existing hydroponic education promotion by XFarm House, thus necessitating an analysis and strengthening of targeted communication strategies. The problem statement for this activity encompasses three main aspects: what are the current communication strategies for hydroponic education promotion implemented by XFarm House what are the inhibiting and supporting factors in hydroponic education promotion communication, and which communication media or channels are most effective in reaching the target audience in the Pamulang area within the context of education. The implementation method was carried out through a participatory approach with stages including observation, interviews, communication situation analysis, and training on digital media-based promotion strategies. The results of the activity indicate that the communication strategies used are still conventional and have not fully utilized the potential of digital media. Supporting factors identified include community enthusiasm for urban farming and an educative environmental setting, while inhibiting factors include limitations in human resources and media management capabilities. Through this activity, the community service team successfully assisted XFarm House in designing more effective and audience-needs-based communication strategies, enabling hydroponic education promotion to run more optimally and sustainably.